Pembangunan Fasilitas Umum Dan Menjaga Kesehatan Lingkungan Dalam Pencegah Penyebaran Virus Covid – 19 - Josephine Roosandriantini; Johana Raycia Aramus Putri (ABIDUMASY, 2021)
In 2019, the country of Indonesia experienced a period of the Covid-19 virus pandemic, which prompted the government to make new policies to prevent the spread of Covid-19. Since 2020, Indonesia has implemented a normal and health protocol called 5M (the mandatory wearing of masks, mandatory washing of hands with soap and running water, obligatory distancing, avoiding crowds, and limiting mobilization and interaction). Protecting the environment, building village public facilities, and re-implementing health protocols are one of the steps in preventing the spread of the Covid-19 virus and producing a healthy environment. By using the method of interaction between residents related to the covid-19 virus, this activity is expected to be able to prevent the spread of the covid-19 virus and produce a healthy environment. This community service activity carried out spraying of disinfectants, fogging, distribution of masks and antiseptic handwashing soap, making hand washing stations, and also painting roads to beautify the village..